CDC yellow book 2026 : health information for international travel - Halsey, Eric (Oxford University Press, 2025)
The CDC Yellow Book has been a trusted resource among healthcare professionals for over half a century. It compiles the US government's current travel health guidance, providing travel medicine specialists, healthcare professionals, and travelers with expert guidance for safe and healthy international travel. Along with disease-specific prevention and treatment recommendations, this comprehensive reference text equips readers with the background and context needed to understand and address public health threats associated with all types of international travel.